Peran BUMDes dalam Pengembangan Potensi Ekonomi Melalui Penanaman Jagung (Studi Pada BUMDes Desa Cege Kecamtan Mare) - Kasnaini; Sitti Nikmah Marzuki; Shadriyah (Journal Financial, Business and Economics, 2024)
This study aims to examine the role of Village-Owned Enterprises (BUMDes) in developing economic potential through corn cultivation and its impact on the economic development of the community in Cege Village, Mare District. This research employs a qualitative approach, utilizing observation and interviews for data collection. The data sources include both primary and secondary data, which are processed through several stages: data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that BUMDes plays a crucial role as a facilitator in enhancing the economic potential of Cege Village through corn cultivation. This role is reflected in the provision of financial capital, high-quality seeds, fertilizers, pesticides, and technical training for corn farmers. These contributions directly impact increased harvest yields and farmer productivity, ultimately improving income and community welfare. Furthermore, the impact of corn cultivation on the economic potential of the Cege Village community is significant. It not only boosts income but also strengthens social ties among farmers and fosters community solidarity.